Optical reconstructive treatment of a patient with essential mesodermal dystrophy of the iris - N. P. Sobolev; S. A. Borzenok; M. A. Soboleva; Yu. V. Shkandina; E. P. Sudakova (Российский офтальмологический журнал, 2021)
Essentially mesodermal iris dystrophy (EMID) is a type of iridocorneal endothelial syndrome and has a chronic progressing character. It is observable after a local fibrosis is formed in the outer border of the iris, which subsequently causes the peripheral iris to pull up and leads to pupil deformation.Purpose: to evaluate the outcome of modern high-tech surgical treatment, which improves visual functions, prevents the decompensation of intraocular pressure and ensures a cosmetic effect.Materials and methods. Patient R., 48 yrs, was diagnosed with OU EMID, low hyperopia, astigmatism, and presbyopia. In order to prevent the development of secondary glaucoma and correct refractive anomalies, the patient was subjected to phacoemulsification with implantation of a multifocal toric IOL, synechiotomy, and iris plastic surgery. MTIOL was calculated using the VERION™ Image Guided System navigation computing complex (Alcon, USA) and the IOLMaster® 700 optical biometer (Carl ZEISS, Germany).Results. In early post-surgery period, the patient noted an increase in visual acuity, stabilized by the 6th month, a significant decrease of undesirable optical phenomena (glare, halo) and was satisfied with the postoperative cosmetic result. The level of intraocular pressure also stabilized by the 6th month after surgery and remained within the reference range by the 9th month. No intraoperative complications were observed. Control UBM scans showed transparent OU cornea, anterior chamber being shallower than the average depth, exfoliated stroma of the iris, moderate anterior chamber angle, intact ciliary body, centrally located pupil, IOL in capsule bag.Conclusion. The case describes a successful outcome of surgical treatment of a rare variety of iridocorneal endothelial syndrome, increase in visual functions, achievement of the desired cosmetic effect, and improvement in the quality of life of the working age patient.